Diversity Scaling Analysis of Chinese Gut Microbiomes Across Ethnicities and Lifestyles - Xiao, Wanmeng; Gao, Depei; Chen, Hongju (Daisy); Qiao, Yuting; Ma, Zhanshan (Sam); Duan, Lincan (Frontiers in Microbiology, 2021)
Diversity scaling (changes) of human gut microbiome is important because it measures the inter-individual heterogeneity of diversity and other important parameters of population-level diversity. Understanding the heterogeneity of microbial diversity can be used as a reference for the personalized medicine of microbiome-associated diseases. Similar to diversity per se, diversity scaling may also be influenced by host factors, especially lifestyles and ethnicities. Nevertheless, this important topic regarding Chinese populations has not been addressed to our best knowledge. Here, we fill the gap by applying a recent extension to classic species-area relationship (SAR), i.e., DAR (diversity-area relationship), to reanalyze a large dataset of Chinese gut microbiomes covering 7 biggest Chinese ethnic groups (covering >95% Chinese) living in rural and urban lifestyles. Four DAR profiles were constructed to investigate the diversity scaling, diversity overlap, potential maximal diversity, and the ratio of local to global diversity, of Chinese gut microbiomes. We discovered: (i) The diversity scaling parameters (z) at various taxon levels are little affected by either ethnicity or lifestyles, as exhibited by less than 0.5% differences in pair-wise comparisons. (ii) The maximal accrual diversity (potential diversity) only exhibited difference in only about 5% of pair-wise comparisons, and all of the differences occurred in ethnicity comparisons (i.e., lifestyles had no effects). (iii) Ethnicity seems to have stronger effects than lifestyles across all taxon levels and this may reflect the reality that China has been experiencing rapid urbanization in the last few decades, while the ethnic-related genetic background may change relatively little during the same period.